Effect of Supplementation with Antioxidants on the Quality of Bovine Milk and Meat Production - Cristina Castillo; Víctor Pereira; Ángel Abuelo; Joaquín Hernández (The Scientific World Journal)
From a clinical point of view, oxidative stress (OS) is considered the primary cause of numerous metabolic processes in transition cow. Thus, the addition of antioxidants has been considered a palliative or preventive treatment. But beyond the clinical perspective, antioxidant supplementation provides an added value to the product obtained being either milk or meat. This paper reviews the beneficial aspects that provide antioxidant supplementation on quality of both products and that fit into the new concept that the consumer has a functional and healthy food. Our approach is from a veterinary standpoint, by reviewing the studies conducted to date and the new perspectives that are interesting and need to be studied in the following years. One of the highlights is that sustainable farming, one in which production is combined with animal health, also impacts positively on the quality of the final products, with beneficial antioxidant properties to human health.